A comparison of selected biomechanical parameters in speed-endurance athletes - Kawalek, K.; Ogurkowska, M. B. (Trends in Sport Sciences, 2014)
Sports can be divided according to different disciplines or types of physical efforts involved. Long-term sport training leads to adaptive changes in the human body, which can result in spinal overload syndrome. The knowledge of the biomechanics of a given sport helps to protect athletes from this spinal disorder. Aim of Study. Using data from available literature an attempt was made to compare two different sports: field hockey and fencing in terms of their biomechanical properties. Results. The two sports share a number of similarities. Firstly, both may involve significant overloads of the lumbar spine because of the performance of uncoupled movements. Secondly, the knee joints in players of both sports may also be overloaded mainly because of numerous 90° flexions with rotations. Conclusions. Fencers and field hockey players are exposed to overloads of the spine and the knees. A special prophylactic and therapeutic program should be developed both for novice and elite athletes of both sports.